2020
DOI: 10.3390/v13010048
|View full text |Cite
|
Sign up to set email alerts
|

Limbic Encephalitis Brain Damage Induced by Cocal Virus in Adult Mice Is Reduced by Environmental Enrichment: Neuropathological and Behavioral Studies

Abstract: We previously demonstrated, using the Piry virus model, that environmental enrichment promotes higher T-cell infiltration, fewer microglial changes, and faster central nervous system (CNS) virus clearance in adult mice. However, little is known about disease progression, behavioral changes, CNS cytokine concentration, and neuropathology in limbic encephalitis in experimental models. Using Cocal virus, we infected C57Bl6 adult mice and studied the neuroanatomical distribution of viral antigens in correlation wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 74 publications
(110 reference statements)
0
2
0
Order By: Relevance
“…In cocal virus infection, mice dwelling in standard environment demonstrated significant weight loss and higher mortality as compared with animals exposed to environmental stimulation. Additionally, enriched environment led to better locomotor and exploratory activity associated with less neuroinvasion and reduced microglial reactivity, revealing that enriched environment drives a more effective immune response in a mouse model of virus encephalitis [90].…”
Section: Environmental Enrichmentmentioning
confidence: 98%
“…In cocal virus infection, mice dwelling in standard environment demonstrated significant weight loss and higher mortality as compared with animals exposed to environmental stimulation. Additionally, enriched environment led to better locomotor and exploratory activity associated with less neuroinvasion and reduced microglial reactivity, revealing that enriched environment drives a more effective immune response in a mouse model of virus encephalitis [90].…”
Section: Environmental Enrichmentmentioning
confidence: 98%
“…SARS-CoV-2 has been found to invade the brain via the olfactory, gustatory, and trigeminal pathways, especially at the early stage of infection (Liu J. M. et al, 2021). Its neuroinvasion route through nasal epithelium (Yachou et al, 2020) is similar to that of many other RNA viruses (Freitas et al, 2020;Awogbindin et al, 2021), including the Piry arbovirus used to infect the mouse prion disease model (de Sousa et al, 2015). We found that the Piry virus interaction with ME7-associated chronic neurodegeneration induces progressive exacerbation of microglia and astrocyte morphological alterations.…”
Section: Infection and Chronic Neurodegenerationmentioning
confidence: 76%